Exploring Older Men's Intergenerational Friendships: Masculinities, Ageing and Ageism - Elliott O'Dare, Catherine (Policy Press, 2023)
The importance and benefits of friendship to the well-being of older adults has been extensively explored in research. This chapter examines the social construction of older age and later life by men (aged 65 and over) in the context of a particular ‘type’ of friendship, namely, intergenerational friendships. Intergenerational friendship is understood as a friendship between a younger and a significantly older adult, who are not related. This chapter discusses how older men negotiate age and ageing in their everyday lives, with and through their intergenerational friendships. We conclude that older men do not conform to the representations of older people as being disengaged and a ‘burden’. Within the realm of ageing masculinities and intergenerational friendship, these men perceive themselves as an equal ‘partner’, giving, and taking in equal measure, challenging expectations of what older people ‘should’ do and be. The research and conclusions presented have implications for policy and practice, in contributing to the understanding of how older men seek enjoyment and belonging in later life.
Ageing, Men and Social Relations
PUBLISHED
Bristol, UK
Keywords: Ageing, ageism, intergenerational solidarity, friendship